Penanganan Longsor Badan Jalan Akibat Gerusan Sungai : Studi Kasus Ruas Jalan Belopa – Batas Kota Palopo Km 333-800 - Amalia, Reski; Nurdin, Abdul Rahim; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2025)
On the Belopa Road Section – Palopo City Boundary KM. 333+800 in Salu Paremang Village, Kamanre District, Luwu Regency, Cilellang area, is a national road that is parallel to the Paremang River, approximately 5-10 meters away. As a result of water scouring during a flood in the Paremang River, it resulted in a downward slide so that the road was eroded and caused half of the road to collapse towards the river. The purpose of this study was to find out how to handle road landslides due to scouring of the Paremang River, and to calculate and analyze the methods of handling landslides on roads due to scouring of the Paremang River. This study uses the method of analysis of soil retaining, the soil retaining used is sheet pile retaining walls. The results of Sheet Pile calculations and analysis, namely the total required Sheet Pile Length is 32 m. The type of Sheet Pile used is Sheet Pile, SP II. As many as 3 rods per setting.